PEMANFAATAN KOMIK STRIP SEBAGAI MEDIA BERAPRESIASI SISWA KELAS VIII A SMP NEGERI 2 KALIWUNGU PADA TOKOH WAYANG PANDAWA - Kristiawan, Novianto Bagus (Eduarts: Jurnal Pendidikan Seni, 2015)
The problem in this research are: (1) how the comic strip form which can be used as a medium of learning appreciation puppet characters Pandavas in VIII A student of SMPN 2 Kaliwungu? (2) how to increase the appreciation of the ability of the puppet characters Pandavas in class VIII A SMP N 2 Kaliwungu using the medium of the comic strip? .Penelitian Using methods Research and Development with controlled observation. Data analysis was performed through data reduction, data presentation and verifikasi.Hasil study shows that an effective form of comic strip as a medium of learning appreciation of the Pandavas leather puppet characters kartunal approach to supporting the comic strip character, load the material appreciation of the puppet characters Pandavas. Use of the comic strip is done by stages: planning, namely teachers and researchers to collaborate in the preparation of the RPP.